Linking human behaviour to environmental effects using a case study of urban rodent control - Morzillo, Anita T; Mertig, Angela G (International journal of environmental studies, 2011)
Pest control is common in many land use activities and can affect non‐target species. Our objectives were to evaluate, among chemical rodent control product (rodenticide) users, awareness of non‐target effects on wildlife and willingness to change rodent control behaviour given knowledge of possible local non‐target effects. Approximately half of respondents to a resident survey in California (USA) practised rodent control; of these, approximately 45% were chemical rodenticide users. Few (10%) were aware of possible non‐target effects. Then, we asked subjects about their potential to pursue each of four rodent control behaviours: continue current use, change product use, reduce use, or stop use. Most respondents indicated that they were most likely to change their rodent control behaviour given the knowledge that rodenticides were possibly affecting non‐target wildlife. Among the four behaviours, the greatest frequency of respondents indicated a potential change of product(s) used. Concern about rodenticides affecting wildlife was the most consistent predictor of potential to change or not change behaviour. Our results highlight importance of awareness about environmental effects of personal actions, and promotion of stewardship may be most effective if efforts focus on development of long‐term personal value in the environment.